2020
DOI: 10.2196/18545
|View full text |Cite
|
Sign up to set email alerts
|

App-Based Delivery of Clinical Emotional Freedom Techniques: Cross-Sectional Study of App User Self-Ratings

Abstract: Background The burgeoning area of mobile health (mHealth) has experienced rapid growth in mobile apps designed to address mental health issues. Although abundant apps offer strategies for managing symptoms of anxiety and stress, information regarding their efficacy is scarce. Objective This study aimed to assess the effect of an mHealth app on user self-ratings of psychological distress in a sample of 270,461 app users. The Tapping Solution App guides u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 74 publications
(108 reference statements)
0
14
0
Order By: Relevance
“…. (Church et al, 2020a). A meta-analysis found similar outcomes for several psychological conditions whether the interventions were conducted virtually or in person (Fernandez et al, 2021).…”
Section: Virtual Eftmentioning
confidence: 96%
See 1 more Smart Citation
“…. (Church et al, 2020a). A meta-analysis found similar outcomes for several psychological conditions whether the interventions were conducted virtually or in person (Fernandez et al, 2021).…”
Section: Virtual Eftmentioning
confidence: 96%
“…The dominant EFT app is called the Tapping Solution. Between October 2018 and October 2019, data were gathered from 270,461 app users (Church et al, 2020a). It was found that across 12 tapping meditations targeting anxiety and stress, users reported a 44% reduction in symptoms (p < 0.001).…”
Section: Anxietymentioning
confidence: 99%
“…More than 120 clinical trials demonstrate the efficacy of acupoint tapping as a psychotherapeutic intervention, often with unusual speed and durable outcomes ( Feinstein, in press ). A recent meta-analysis has shown that acupoint tapping is an essential ingredient for these strong effects ( Church et al, 2020 ). The studies reviewed compared acupoint tapping protocols with otherwise identical protocols except that a different intervention—such as diaphragmatic breathing or tapping on “sham points”—was substituted for the acupoint tapping component.…”
Section: The Nature Of Energy Psychologymentioning
confidence: 99%
“…The ACEP Humanitarian Committee’s “Resources for Resilience” program posts a variety of online tools that can help “alleviate suffering by teaching self-help techniques to those experiencing the effects of violence, trauma, and natural disasters” (see text footnote 7). A cell phone app that guides users in applying acupoint tapping protocols for anxiety and stress was investigated in a large-scale study including 270,461 app users and found highly significant ( p < 0.001) symptom reduction ( Church et al, 2020 ).…”
Section: Efficient Delivery Of Energy Psychology Servicesmentioning
confidence: 99%
“…Energy psychology protocols have been successfully applied in the self-management of stress [31], anxiety [24], and symptoms of fibromyalgia [65]. A mobile app that guides users in applying acupoint tapping protocols for anxiety and stress was investigated in a large-scale study including 270,461 app users and found highly significant (p<0.001) symptom reduction [66].…”
Section: Back-home Applicationsmentioning
confidence: 99%